An Empirical Analysis of Social Dimension Factors Towards Better IT Service Quality for Malaysian Public Agencies - Hanzah, Norhafizah; Sulaiman, Hidayah (International Journal of Engineering and Technology, 2018)
Information technology (IT) has become an important part in enabling business decisions and strategies in organizations. The IT unit established in various organizations is responsible to ensure that different business units receive the expected level of technical assistance which they require. However, in many cases, the common understanding between business and IT is rarely achieved. This leads to the debate on how business and IT can be aligned in ensuring better IT services is provided to the end-users. Hence, there is a need to identify critical social factors that lead to better alignment thus leads to better service quality. This paper aims to conceptualize how business-IT alignment would have the impact to IT services through the social aspects of cognition, shared knowledge, and communication. A model is derived from the findings of the literatures and tested within the domain of the Malaysian agriculture public sectors using quantitative method. Results indicate that there are positive impacts of social dimensions towards business-IT alignment and thus has a significant impact towards IT service quality. This model reveals the insight on the importance of social alignment dimension factors in achieving better IT service quality in government agency setting.Â